A road surface cold patch and a preparation method thereof

CN122940409APending Publication Date: 2026-10-20KESHUN WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098946.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]本发明提供一种路面冷补料及其制备方法,用以解决现有技术中路面冷补料粘接性能不佳、易剥落以及抗热氧老化和抗紫外老化性能差等问题

Benefits of technology

本发明提供的路面冷补料具有高马歇尔稳定度、高粘接强度、耐水、耐紫外和耐老化等多重优点,有效延长了路面修复体的使用寿命,降低了养护成本。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to the field of highway maintenance technology, and more particularly to a cold pavement patch material and its preparation method. The raw materials for preparing the cold pavement patch material provided by this invention include base asphalt, a polymer modifier, a phenolic acid antioxidant, aggregates, polycyclic carboxylic acid modified xylene-formaldehyde resin, a solvent, an active filler, and a diluent. The weight ratio of the phenolic acid antioxidant to the polycyclic carboxylic acid modified xylene-formaldehyde resin is (0.2-1):(2-5). The cold pavement patch material provided by this invention has multiple advantages, including high Marshall stability, high bond strength, water resistance, UV resistance, and aging resistance, effectively extending the service life of pavement repairs and reducing maintenance costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of highway maintenance technology, and in particular to a cold pavement patching material and its preparation method. Background Technology

[0002] Asphalt pavements are widely used due to their advantages such as comfortable driving, low noise, and ease of maintenance. However, under the combined effects of traffic loads and natural environmental factors (such as temperature changes, rain, and ultraviolet radiation), asphalt pavements inevitably develop defects such as cracks, potholes, and loosening. To ensure traffic safety and extend the service life of roads, timely and effective repair of these defects is crucial.

[0003] Cold pavement patching material has become a commonly used repair material for routine pavement maintenance and emergency repairs due to its outstanding advantages such as requiring no heating, simple construction, all-weather use, and rapid reopening to traffic. It is a pre-mixed asphalt mixture that can be stored and used for a long time at room temperature.

[0004] However, existing conventional cold patching materials for road surfaces still face some technical bottlenecks during use, mainly in the following aspects: (1) The adhesion between asphalt and aggregate in traditional cold patch materials is limited. Especially in rainy weather or humid environments, moisture can easily penetrate the interface between asphalt and aggregate, causing the asphalt film to peel off from the aggregate surface. This peeling will severely weaken the internal structural strength of the mixture, making the edges of the repaired potholes easy to loosen and the whole pothole easy to be carried out by wheels, resulting in a short service life of the repair body, requiring frequent secondary repairs, increasing maintenance costs and traffic disruption.

[0005] (2) As an organic polymer material, asphalt is sensitive to environmental factors. The asphalt components in existing cold patch materials will age in the external environment. On the one hand, thermo-oxidative aging will occur under high temperature and oxygen, causing the asphalt to harden, become brittle, and lose its elasticity. On the other hand, ultraviolet radiation from sunlight is a key factor causing asphalt aging. It can trigger photochemical reactions inside the asphalt, destroy its chemical structure, and cause rapid deterioration of material properties, manifested as surface cracking, powdering, and decreased strength. Most cold patch materials on the market at present do not adequately consider resistance to ultraviolet aging, resulting in rapid performance degradation and unsatisfactory durability under outdoor exposure conditions.

[0006] Therefore, how to overcome the shortcomings of existing cold pavement patch materials, such as poor adhesion, easy peeling, and poor resistance to thermo-oxidative aging and ultraviolet aging, and develop a new type of cold pavement patch material with high adhesion strength, excellent water resistance and excellent anti-aging properties, has become an urgent technical problem to be solved in this field. Summary of the Invention

[0007] This invention provides a cold pavement patch material and its preparation method, which solves the problems of poor adhesion, easy peeling, and poor resistance to thermo-oxidative aging and ultraviolet aging in the prior art.

[0008] According to a first aspect of the present invention, the present invention provides a cold pavement patch material, the raw materials for which include base asphalt, polymer modifier, phenolic acid antioxidant, aggregate, polycyclic carboxylic acid modified xylene formaldehyde resin, solvent, active filler and diluent, wherein the weight ratio of the phenolic acid antioxidant to the polycyclic carboxylic acid modified xylene formaldehyde resin is (0.2-1):(2-5).

[0009] In this invention, base asphalt serves as the basic binder, forming the main body of the mixture together with aggregates as the skeleton. Polymer modifiers improve the high and low temperature performance and elasticity of the asphalt. Phenolic acid antioxidants effectively scavenge free radicals at the molecular level, fundamentally inhibiting asphalt aging caused by heat, oxygen, and ultraviolet radiation, thus endowing the material with excellent chemical durability. Polycyclic carboxylic acid-modified xylene-formaldehyde resin significantly improves the cohesive strength, adhesion to aggregates, and overall toughness of the mixture by constructing a strong and tough three-dimensional network structure. Solvents assist in the uniform dispersion of the polymer modifiers. Active fillers enhance resistance to water damage and provide secondary strength. A diluent ensures the workability of the material at room temperature. The cold-pavement material provided by this invention achieves a dual synergistic effect of chemical anti-aging and physical structural enhancement by synergistically compounding a specific ratio of phenolic acid antioxidants with polycyclic carboxylic acid-modified xylene-formaldehyde resin. The synergistic effect of these two components with other components gives this cold pavement patch material not only high bonding strength and excellent mechanical properties, but also outstanding resistance to thermal aging and UV aging. This effectively solves the technical problems of traditional cold pavement patch materials being prone to peeling and having poor durability, and significantly extends the service life of the pavement repair body.

[0010] The cold pavement patch material according to the present invention comprises, by weight, the following raw materials: 10-25 parts of base asphalt, 0.3-3 parts of polymer modifier, 0.2-1 parts of phenolic acid antioxidant, 50-75 parts of aggregate, 2-5 parts of polycyclic carboxylic acid modified xylene formaldehyde resin, 2-5 parts of solvent, 2-5 parts of active filler, and 1-5 parts of diluent.

[0011] In the above scheme, by limiting the amount of each component within a reasonable range, the components can exert a more significant synergistic effect, thereby better improving the overall performance of the cold patching material for road surfaces.

[0012] In this invention, the base bitumen is 10-25 parts, for example, 10 parts, 12 parts, 15 parts, 20 parts, 25 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0013] In this invention, the polymer modifier is 0.3-3 parts, for example, it can be 0.3 parts, 0.5 parts, 1.0 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, etc., and of course, it can also be other values ​​within the above range, which are not limited here.

[0014] In this invention, the phenolic acid antioxidant is 0.2-1 parts, for example, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1.0 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0015] In this invention, the aggregate is 50-75 parts, for example, it can be 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, etc., and of course it can also be other values ​​within the above range, which are not limited here.

[0016] In this invention, the amount of polycyclic carboxylic acid-modified xyleneform resin is 2-5 parts, for example, 2 parts, 2.5 parts, 3 parts, 4 parts, 5 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Preferably, the polycyclic carboxylic acid is a diterpenoid carboxylic acid. More preferably, the diterpenoid carboxylic acid is derived from rosin.

[0017] In this invention, the solvent is 2-5 parts, for example, 2 parts, 2.5 parts, 3 parts, 4 parts, 5 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0018] In this invention, the active filler is 2-5 parts, for example, 2 parts, 3 parts, 3.5 parts, 4 parts, 5 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0019] In this invention, the diluent is 1-5 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, etc., and of course, other values ​​within the above range are also possible, which are not limited here.

[0020] According to the cold pavement patch material of the present invention, the phenolic acid antioxidant is ferulic acid; and the polycyclic carboxylic acid modified xylene-formaldehyde resin is RX80 resin.

[0021] In this invention, ferulic acid, as a highly efficient natural phenolic acid antioxidant, possesses a phenolic hydroxyl structure that can effectively capture and eliminate destructive free radicals generated in asphalt due to light, heat, and oxygen. This fundamentally breaks the chain reaction of asphalt aging, protects the chemical structural stability of asphalt molecules, and maintains the material's inherent flexibility. Meanwhile, RX-80 resin is a polycyclic carboxylic acid-modified xylene-formaldehyde resin that combines the excellent adhesion and compatibility of rosin with the hardness and heat resistance of xylene-formaldehyde resin through esterification. It forms a strong, interpenetrating three-dimensional polymer network structure in asphalt. This network not only significantly enhances the cohesive strength, toughness, and adhesion of the asphalt mixture, forming a robust framework, but also acts as a barrier, preventing the penetration of external oxygen and moisture into the material. The chemical protection provided by ferulic acid delays the aging and embrittlement of the asphalt matrix and the RX-80 resin network itself, while the strong physical network of RX-80 resin provides durable structural support for the material and creates a more stable environment for ferulic acid. The combination of these two components achieves a better synergistic effect, realizing multi-dimensional protection from the inside out, making the overall durability and anti-aging performance of the cold patch material far exceed that of a single component. Experiments showed that replacing ferulic acid with other acids (cinnamic acid, oxalic acid) significantly reduced the product's compressive strength, heat aging retention rate, and UV aging resistance. Replacing RX-80 resin with ordinary resin significantly reduced Marshall stability, bond strength, and anti-aging properties.

[0022] According to the cold pavement patch material of the present invention, the aggregate is modified basalt aggregate; the modified basalt aggregate is obtained by immersing basalt aggregate in an aqueous solution of silane coupling agent for activation and modification.

[0023] In the above scheme, the silane coupling agent acts as a modifier, chemically bonding one end to the hydroxyl groups on the basalt surface, while the organic functional groups at the other end interact strongly with the asphalt. This transforms the aggregate surface from hydrophilic to hydrophobic and oleophilic, forming a strong and water-resistant transition layer at the asphalt-aggregate interface. This enhances the adhesion between the asphalt and aggregate, significantly improving the mixture's resistance to water damage and spalling, thereby increasing the overall structural strength and long-term durability of the cold-patch pavement, especially in humid and rainy environments, effectively ensuring repair results.

[0024] According to the cold pavement patch material of the present invention, the basalt aggregate is a screened and graded material, wherein the mass proportion of the material with a particle size of 9.5mm-13.2mm is 30-40%, the mass proportion of the material with a particle size of 4.75mm-9.5mm is 30-40%, the mass proportion of the material with a particle size of 2.36mm-4.75mm is 15-25%, the mass proportion of the material with a particle size of less than 2.36mm is 8-12%, and the sum of the mass proportions of the materials of each particle size is 100%.

[0025] Preferably, the pH value of the aqueous solution of the silane coupling agent is 4-5, and the mass percentage of the silane coupling agent is 1-5%; the silane coupling agent is one or both of γ-glycidoxypropyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane. By precisely controlling the key parameters of the modification process, the modification effect on the aggregate surface can be improved.

[0026] More preferably, the activation modification temperature is 50-60℃ and the time is 1-2 hours. This optimized temperature-time combination can improve the interface modification effect and maximize the bond strength and durability between asphalt and aggregate.

[0027] According to the cold patch material for road surfaces of the present invention, the active filler is calcium oxide. Calcium oxide, as a highly efficient moisture scavenger and anti-stripping agent, can undergo an irreversible chemical reaction with trace amounts of moisture present on the aggregate surface or in the system to generate calcium hydroxide. This eliminates the potential damage of moisture to the asphalt-aggregate interface. The in-situ generated calcium hydroxide can improve the surface chemical properties of the aggregate and enhance the chemical adsorption between asphalt and aggregate, thereby greatly improving the water damage resistance and anti-stripping performance of the mixture. Furthermore, as a fine filler, calcium oxide can fill the asphalt mastic, improving the stiffness and modulus of the asphalt mastic through physical filling and chemical reaction with the acidic components of asphalt, thus enhancing the overall structural strength and deformation resistance of the cold patch material.

[0028] Preferably, the calcium oxide has a mesh size of 500-1000 mesh.

[0029] According to the cold pavement patch material of the present invention, the base asphalt is one or both of 70# asphalt and 90# asphalt; the polymer modifier is selected from one or more of styrene-butadiene rubber and hydrogenated styrene-butadiene block copolymer; the solvent is selected from one or more of aromatic oil, anti-corrosion oil and rubber oil; and the diluent is selected from one or more of acetone, carbon tetrachloride and ethyl acetate.

[0030] The cold pavement patch material according to the present invention, by weight, further comprises the following raw materials: 0.2-1 parts of high-temperature additive. By introducing a specific amount of high-temperature additive, the present invention can significantly improve the high-temperature stability and resistance to permanent deformation of the cold pavement patch material.

[0031] Preferably, the high-temperature additive has a viscosity of 100-500 mPa·s at 130°C, a softening point of 100-120°C, a number-average molecular weight of 1200-3000 g / mol, and an acid value of 13-20.

[0032] More preferably, the high-temperature additive is selected from one or more of oxidized polyethylene wax and amide wax powder. These high-temperature additives can form a microcrystalline network structure in asphalt. Under high-temperature conditions, this rigid network structure can greatly improve the stiffness and high-temperature viscosity of the asphalt mortar, effectively constrain the fluidity of the asphalt, improve its Marshall stability, and ensure that the repair body is not prone to softening, pushing, and deformation under high temperatures and heavy traffic in summer, thereby ensuring the long-term structural stability and smoothness of the repaired area.

[0033] The cold pavement patch material according to the present invention further includes, by weight, the following raw materials: 2-8 parts of silicate cement.

[0034] This invention introduces a specific amount of silicate cement. As an inorganic cementitious material, silicate cement undergoes a slow hydration reaction with trace amounts of moisture infiltrating the system and environment after cold patching and compaction. This reaction can improve the later cohesive strength, load-bearing capacity, and wear resistance of the repair. The hydration reaction can also actively consume moisture that is harmful to the asphalt-aggregate adhesion interface, thereby further enhancing the material's resistance to water damage. It also works synergistically with anti-stripping agents such as calcium oxide to ensure the long-term stability of the repair in humid environments.

[0035] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned cold pavement patch material, comprising the following steps: mixing base asphalt and solvent, adding polymer modifier, polycyclic carboxylic acid modified xylene formaldehyde resin, phenolic acid antioxidant, aggregate and active filler, stirring and reacting at 180-190°C, and then adding diluent and mixing.

[0036] The preparation method provided by this invention involves the blending reaction of components at a high temperature of 180-190℃. This temperature not only ensures that high-viscosity, high-molecular-weight components such as polymer modifiers and polycyclic carboxylic acid modified xylene formaldehyde resin fully swell, disperse, and form a stable three-dimensional network structure in asphalt, but also ensures that functional additives such as phenolic antioxidants can be uniformly dissolved in the asphalt phase, thereby preparing a high-performance cold pavement patch.

[0037] The method for preparing cold pavement patching material according to the present invention includes the following steps: Mix the base asphalt and solvent at 150-160℃; add the polymer modifier and stir at 180-190℃ for 1-3 hours; add the polycyclic carboxylic acid modified xylene-formaldehyde resin and stir at 180-190℃ for 0.5-1 hours; add the phenolic acid antioxidant and stir at 180-190℃ for 0.5-2 hours; add the aggregate and stir at 180-190℃ for 0.5-1 hours; add the active filler and stir at 180-190℃ for 1-2 hours; cool to 50-80℃, add the diluent, and stir to mix for 0.5-2 hours.

[0038] The above preparation method employs a step-by-step, temperature-zone-specific, and precisely time-controlled process. Utilizing a high-temperature zone of 180-190℃, the precise control of the order of addition and stirring time of each polymer component ensures their full swelling, dispersion, and formation of a stable and synergistic reinforcing network in the asphalt, while also guaranteeing the uniform dissolution of additives such as phenolic acid antioxidants. Subsequently, mixing aggregates and active fillers at this high temperature ensures the high-performance modified asphalt mastic's impregnation and firm coating of the aggregates.

[0039] The beneficial effects of this invention are: The cold pavement patch material provided by this invention has multiple advantages such as high Marshall stability, high bonding strength, water resistance, UV resistance and aging resistance, which effectively extends the service life of pavement repairs and reduces maintenance costs. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0041] The raw materials used in the following examples and comparative examples are sourced from the following sources: 70# / 90# asphalt was purchased from Shandong Jingbo Petrochemical Co., Ltd. SBR grade 095 was purchased from Haifang Technology Company; SEBS grade 1901H was purchased from Yueyang Baling Petrochemical Company. The oxidized polyethylene wax, C9703, has a viscosity of 250 mPa·s at 130℃, a softening point of 114℃, a number-average molecular weight of 1300 g / mol, and an acid value of 18. It was purchased from Guangdong Qiaoxing Company. Ferulic acid, cinnamic acid, oxalic acid, acetone, carbon tetrachloride, and ethyl acetate were reagent-grade and purchased from Maclean's Reagent Company. The basalt aggregate is a screened and graded material, with the following mass percentages: 35% for particles with a diameter of 9.5mm-13.2mm, 35% for particles with a diameter of 4.75mm-9.5mm, 20% for particles with a diameter of 2.36mm-4.75mm, and 10% for particles with a diameter less than 2.36mm. The raw materials were purchased from Lanzhou Jiang'en Construction Engineering Co., Ltd. Silane coupling agents KH560 and KH570 were purchased from Hangzhou Jessica Chemical Co., Ltd. RX80 resin, purchased from Guangzhou Liben Rubber Co., Ltd. C5 resin, purchased from Guangzhou Kaitian Chemical Co., Ltd. Xylene-formaldehyde resin was purchased from Jining Huakai Resin Company. The calcium oxide was 800 mesh and was purchased from Heshan Han Color Masterbatch Co., Ltd. Trihydrate, 400 mesh, purchased from Jiangxi Guangyuan Company; Silicate cement, purchased from Chongqing Yinghao Trading Co., Ltd.; The aromatic oil, grade X1820, was purchased from Guangdong Dagang Company.

[0042] In the following examples and comparative examples, the component amounts are all expressed in parts by weight. Unless otherwise specified, each part by weight is 1 g.

[0043] Example 1 This embodiment provides a cold pavement patching material, comprising the following raw materials in parts by weight: The composition includes 20 parts of 70# asphalt, 1 part of SEBS, 1 part of oxidized polyethylene wax, 0.6 parts of ferulic acid, 70 parts of modified basalt aggregate, 3 parts of RX80 resin, 3 parts of aromatic oil, 3 parts of calcium oxide, 5 parts of silicate cement, and 3 parts of diluent. The modified basalt aggregate is prepared by immersing ultrasonically cleaned basalt in a 3wt% silane coupling agent KH560 aqueous solution at pH 4.5, stirring and activating at 55℃ for 1.5 hours, followed by filtration, washing, and drying. The diluent is acetone.

[0044] This embodiment also provides a method for preparing the cold patching material for road surfaces, including the following steps: Add the base pitch and aromatic oil to the reaction vessel while stirring and heating at 150-160℃; Add the polymer modifier and heat at 180-190℃ with stirring for 2 hours; Add RX80 resin and high-temperature additives, heat at 180-190℃ and stir for 0.5 hours; Add ferulic acid and heat and stir at 180-190℃ for 1 hour; Add modified basalt aggregate, heat at 180-190℃ and stir for 0.5 hours; Add calcium oxide and silicate cement, heat at 180-190℃ and stir for 1 hour; Cool to 50-80℃, add diluent, stir thoroughly for 1 hour to make cold pavement patch material.

[0045] Example 2 This embodiment provides a cold pavement patching material, comprising the following raw materials in parts by weight: 17 parts of 90# asphalt, 1.5 parts of SBR, 0.5 parts of oxidized polyethylene wax, 1 part of ferulic acid, 65 parts of modified basalt aggregate, 5 parts of RX80 resin, 5 parts of aromatic oil, 2 parts of calcium oxide, 3 parts of silicate cement, and 2 parts of diluent.

[0046] This embodiment provides a method for preparing the cold patching material for road surfaces, which is the same as in Embodiment 1.

[0047] Example 3 This embodiment provides a cold pavement patch material, which differs from Embodiment 1 in that it uses untreated basalt aggregate of equal mass and gradation to replace modified basalt aggregate.

[0048] This embodiment provides a method for preparing the cold patching material for road surfaces, which is the same as in Embodiment 1.

[0049] Example 4 This embodiment provides a cold patching material for road surfaces, which differs from Embodiment 1 in that it uses an equal mass of heavy calcium carbonate instead of calcium oxide.

[0050] This embodiment provides a method for preparing the cold patching material for road surfaces, which is the same as in Embodiment 1.

[0051] Example 5 This embodiment provides a cold pavement patching material, comprising the following raw materials in parts by weight: The ingredients are: 10 parts 70# asphalt, 1 part SBR, 0.2 parts oxidized polyethylene wax, 0.2 parts ferulic acid, 50 parts modified basalt aggregate, 5 parts RX80 resin, 2 parts aromatic oil, 2 parts calcium oxide, 8 parts silicate cement, and 1 part diluent. The diluent is carbon tetrachloride.

[0052] The preparation method provided in this embodiment is the same as that in Embodiment 1.

[0053] Example 6 This embodiment provides a cold pavement patching material, comprising the following raw materials in parts by weight: The ingredients are: 25 parts 90# asphalt, 3 parts SEBS, 1 part amide wax, 1 part ferulic acid, 75 parts modified basalt aggregate, 5 parts RX80 resin, 5 parts aromatic oil, 5 parts calcium oxide, 8 parts silicate cement, and 5 parts diluent. The diluent is ethyl acetate.

[0054] The preparation method provided in this embodiment is the same as that in Embodiment 1.

[0055] Example 7 This embodiment provides a cold patching material for road surfaces, which differs from Embodiment 1 in that it uses gallic acid of equal mass instead of ferulic acid.

[0056] Comparative Example 1 This comparative example provides a cold patching material for road surfaces, which differs from Example 1 in that it uses an equal mass of cinnamic acid instead of ferulic acid.

[0057] Comparative Example 2 This comparative example provides a cold patching material for road surfaces, which differs from Example 1 in that it uses an equal mass of oxalic acid instead of ferulic acid.

[0058] Comparative Example 3 This comparative example provides a road surface cold patching material, which differs from Example 1 in that an equal mass of C5 resin is used instead of RX80 resin.

[0059] Comparative Example 4 This comparative example provides a road surface cold patching material, which differs from Example 1 in that it uses an equal mass of xylene-formaldehyde resin instead of RX80 resin.

[0060] The cold pavement patching materials of the embodiments and comparative examples were tested according to the following methods: Marshall stability: Samples were prepared and tested in accordance with JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0061] Bond strength: Tested according to JCT 2678-2022.

[0062] Water absorption rate: Samples were prepared and tested according to JCT 2678-2022.

[0063] Compressive strength heat aging retention rate: Samples were prepared and tested in accordance with JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0064] UV aging resistance: The mass loss rate after 168 hours of UV irradiation was tested according to JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0065] The test results are shown in Table 1 below: Table 1 Test Projects / Case Studies Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Marshall stability / KN 10.3 11.4 9.1 9.8 10.1 12.1 10.0 9.6 9.4 8.8 9.1 Bond strength / MPa 1.34 1.51 1.17 1.17 1.27 1.64 1.28 1.21 1.20 1.08 1.02 Water absorption rate / % 3.1 3.5 3.2 3.0 3.4 2.3 3.4 3.7 4.2 3.1 3.6 Compressive strength heat aging retention rate / % 98.2 99.3 97.5 94.7 94.2 99.1 94.7 88.2 86.1 93.2 90.3 Anti-UV aging / % 2.1 1.6 2.5 2.8 3.1 1.9 3.4 5.8 6.3 4.7 5.4 The test results above show that: The cold-paved road patch materials prepared in the various embodiments of this invention possess high strength, high adhesion, excellent water resistance, and outstanding heat and light aging resistance. Specifically, the Marshall stability reaches over 9.1 KN, with a maximum of 12.1 KN; the bond strength is consistently above 1.17 MPa, demonstrating strong cohesion and adhesion; the water absorption rate is less than or equal to 3.5%, exhibiting good resistance to water damage; the compressive strength retention rate during heat aging remains at a high level of over 94%, and the UV aging mass loss rate is controlled below 3.4%.

[0066] Compared with Example 1, after replacing the phenolic antioxidant (ferulic acid) with cinnamic acid in Comparative Example 1 and oxalic acid in Comparative Example 2, the anti-aging performance of the cold patch material for road surface dropped sharply. Its compressive strength heat aging retention rate decreased significantly, and the mass loss rate after UV aging also deteriorated sharply. Mechanical indicators such as Marshall stability and bond strength also decreased, and water absorption increased.

[0067] Compared with Example 1, after replacing the modified xylene-formaldehyde resin (RX80 resin) with the C5 resin of Comparative Example 3 or the ordinary xylene-formaldehyde resin of Comparative Example 4, the mechanical properties and durability of the road cold patch material decreased across the board. The Marshall stability dropped to 8.8-9.1 KN, the bond strength decreased significantly to 1.0-1.1 MPa, and the UV aging resistance also deteriorated significantly.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cold pavement patching material, characterized in that, The raw materials for its preparation include base asphalt, polymer modifier, phenolic acid antioxidant, aggregate, polycyclic carboxylic acid modified xylene formaldehyde resin, solvent, active filler and diluent, wherein the weight ratio of the phenolic acid antioxidant to the polycyclic carboxylic acid modified xylene formaldehyde resin is (0.2-1):(2-5).

2. The cold pavement patching material according to claim 1, characterized in that, The raw materials, by weight, include the following: 10-25 parts of base asphalt, 0.3-3 parts of polymer modifier, 0.2-1 parts of phenolic acid antioxidant, 50-75 parts of aggregate, 2-5 parts of polycyclic carboxylic acid modified xylene formaldehyde resin, 2-5 parts of solvent, 2-5 parts of active filler, and 1-5 parts of diluent.

3. The cold pavement patching material according to claim 1 or 2, characterized in that, The phenolic acid antioxidant is ferulic acid; the polycyclic carboxylic acid modified xylene-formaldehyde resin is RX80 resin.

4. The cold pavement patching material according to any one of claims 1-3, characterized in that, The aggregate is modified basalt aggregate; the modified basalt aggregate is obtained by immersing basalt aggregate in an aqueous solution of silane coupling agent for activation and modification; Preferably, the pH value of the aqueous solution of the silane coupling agent is 4-5, and the mass percentage of the silane coupling agent is 1-5%; the silane coupling agent is one or both of γ-glycidoxypropyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane. More preferably, the activation and modification temperature is 50-60℃ and the time is 1-2h.

5. The cold pavement patching material according to any one of claims 1-4, characterized in that, The active filler is calcium oxide; preferably, the calcium oxide has a mesh size of 500-1000 mesh.

6. The cold pavement patching material according to any one of claims 1-5, characterized in that, The base asphalt is one or both of 70# asphalt and 90# asphalt; the polymer modifier is selected from one or more of styrene-butadiene rubber and hydrogenated styrene-butadiene block copolymer; the solvent is selected from one or more of aromatic oil, anti-corrosion oil and rubber oil; the diluent is selected from one or more of acetone, carbon tetrachloride and ethyl acetate.

7. The cold pavement patching material according to any one of claims 2-6, characterized in that, Based on parts by weight, it also includes the following preparation materials: 0.2-1 parts of high-temperature additives; Preferably, the high-temperature additive has a viscosity of 100-500 mPa·s at 130°C, a softening point of 100-120°C, a number-average molecular weight of 1200-3000 g / mol, and an acid value of 13-20. More preferably, the high-temperature additive is selected from one or more of oxidized polyethylene wax and amide wax powder.

8. The cold pavement patching material according to any one of claims 2-7, characterized in that, The preparation materials also include, by weight, 2-8 parts of silicate cement.

9. The method for preparing the cold pavement patch material according to any one of claims 1-8, characterized in that, The process includes the following steps: mixing the base asphalt and solvent, adding polymer modifier, polycyclic carboxylic acid modified xylene formaldehyde resin, phenolic antioxidant, aggregate and active filler, stirring and reacting at 180-190℃, and then adding diluent and mixing.

10. The method for preparing cold pavement patching material according to claim 9, characterized in that, Includes the following steps: Mix the base asphalt and solvent at 150-160℃; add the polymer modifier and stir at 180-190℃ for 1-3 hours; add the polycyclic carboxylic acid modified xylene-formaldehyde resin and stir at 180-190℃ for 0.5-1 hours; add the phenolic acid antioxidant and stir at 180-190℃ for 0.5-2 hours; add the aggregate and stir at 180-190℃ for 0.5-1 hours; add the active filler and stir at 180-190℃ for 1-2 hours; cool to 50-80℃, add the diluent, and stir to mix for 0.5-2 hours.